Constructing and validating an occupational job strain index based on five Norwegian nationwide surveys of living conditions on work environment - Giang Huong Le; Åsmund Hermansen; Espen Dahl (BMC, 2023)
Abstract Background It has been claimed that Nordic register data are a "goldmine" for research. However, one limitation is the lack of information on working conditions. Job exposure matrices (JEMs) are one solution to this problem. Thus, the three aims of this study were (i) to investigate the reliability of an occupation-based psychosocial JEM, i.e., a Job Strain Index (job strain or JSI abbreviated), (ii) to examine the construct and criterion-related validity of this measure of job strain (iii) and assesses the concurrent and the predictive validity of an occupation-based Job Strain Index for use in analyses of Norwegian register data. Method The study utilized five waves of the nationwide Norway Survey of Living Conditions in the Work Environment with a total sample of 43,977 individuals and register data with a total sample of 1,589,535 individuals. Job strain was composed of items belonging to the two dimensions of Karasek's DC model, job demands and job control (1979). The reliability of the JSI and its dimensions and components were investigated by measuring the degree of agreement (Cohen's kappa), sensitivity, specificity, and internal consistency (Cronbach's alpha). Construct validity was assessed by confirmatory factor analysis, and criterion-related validity was measured by concurrent validity and predictive validity. The selected concurrent criteria were self-reported survey information on long-term sick absence, anxiety, depression, and sleeping difficulty. The predictive criteria were register information on receipt of disability benefits, mortality, and long-term sick leave. Results Agreement between individual and occupation-based job strain and components was fair to poor. The sensitivity and specificity of occupation-based job strain and its components varied from acceptable to low. The consistency of the items comprising job demand and job control was clearly acceptable. Regarding concurrent validity, significant associations between (both individual and occupational) job strain, and long-term sick leave and sleeping difficulty were observed for both genders. Occupation-based job strain indicated an elevated risk for anxiety and depression among men, but not among women. As for predictive reliability, significant associations between occupation-based job strain and all three health outcomes were observed for both men and women. Conclusion Our occupation-based JSI serves as a reliable and valid indicator of psychosocial job exposure that can be used in analyses of Norwegian register data where individual information on such conditions is missing.